Analysis Of The Base Sector Of Sumenep And Sampang Regency In 2016-2020 - Putri, Yuninda Anggraini (Politeknik Keuangan Negara STAN, 2023)
National development is a way to achieve one of the goals of the Indonesian, which is to promote general welfare. Development through the decentralisation system is implemented by giving authority to autonomous regions in terms of local policies to manage their resources and regulate their respective regions. This regional development is also to increase regional independence through Regional Revenue, especially in terms of increasing Regional Original Revenue (PAD) by maximizing the potential of the regional economic sector. However, in reality, there is still an imbalance in regional independence from PAD which plays a small role in regional revenue. This also occurs in East Java Province, with two districts that have PAD contributions of less than ten percent of their regional income, namely Sumenep Regency and Sampang Regency. Therefore, this study aims to determine the economic sectors that can become the base and leading sectors to get attention by their local governments. The potential of the regional sector can be calculated using the Location Quotient (LQ) technique and Shift-Share Analysis, using these techniques it can be seen which sectors are the basic, prospective, advanced, and competitive sectors. Through these techniques, it is found that based on the results of the LQ analysis, both districts have the same basic sector, namely, mining and quarrying. As for the results of the shift-share analysis, it is found that Sumenep Regency has a leading sector in information and communication, while Sampang Regency has a leading sector, namely, the construction sector.